2016
DOI: 10.1128/jvi.00516-16
|View full text |Cite|
|
Sign up to set email alerts
|

Discovery of a Coregulatory Interaction between Kaposi's Sarcoma-Associated Herpesvirus ORF45 and the Viral Protein Kinase ORF36

Abstract: Kaposi's sarcoma-associated herpesvirus (KSHV) is the causative agent of three human malignancies. KSHV ORF36 encodes a serine/threonine viral protein kinase, which is conserved throughout all herpesviruses. Although several studies have identified the viral and cellular substrates of conserved herpesvirus protein kinases (CHPKs), the precise functions of KSHV ORF36 during lytic replication remain elusive. Here, we report that ORF36 interacts with another lytic protein, ORF45, in a manner dependent on ORF36 ki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
31
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(35 citation statements)
references
References 55 publications
4
31
0
Order By: Relevance
“…KSHV ORF36 encodes a serine/threonine viral protein kinase (vPK) conserved among the herpesviruses and has been shown to activate JNK, a MAPK family member (Hamza et al, 2004; Avey et al, 2016; Bhatt et al, 2016). Though vPK is classified as a late lytic gene, it can be expressed in hypoxic conditions.…”
Section: Kshv Orf36/vpk and Its Impact On Pi3k/akt And Mapk Signalingmentioning
confidence: 99%
See 3 more Smart Citations
“…KSHV ORF36 encodes a serine/threonine viral protein kinase (vPK) conserved among the herpesviruses and has been shown to activate JNK, a MAPK family member (Hamza et al, 2004; Avey et al, 2016; Bhatt et al, 2016). Though vPK is classified as a late lytic gene, it can be expressed in hypoxic conditions.…”
Section: Kshv Orf36/vpk and Its Impact On Pi3k/akt And Mapk Signalingmentioning
confidence: 99%
“…Though vPK is classified as a late lytic gene, it can be expressed in hypoxic conditions. Knock down of vPK negatively affects lytic replication and attenuates expression of several late genes (Avey et al, 2016). A ~3 to 10 fold reduction in viral progeny production and infection was observed in deficient or kinase-dead vPK viruses.…”
Section: Kshv Orf36/vpk and Its Impact On Pi3k/akt And Mapk Signalingmentioning
confidence: 99%
See 2 more Smart Citations
“…With BAC16‐based mutagenesis, Fanxiu Zhu et al found that disruption of ORF45 caused a decrease in yield of progeny viruses and reduced infectivity . Furthermore, to investigate the roles of ORF36 that interacts with ORF45 in the context of KSHV lytic replication, they also engineered both ORF36‐null and kinase‐dead mutants by BAC16 system and figured out that ORF36‐null/mutant virions were moderately defective in viral particle production and were further deficient in primary infection . BAC16‐based mutagenesis has also been employed to several studies of KSHV‐encoded 25 mature miRNAs derived from 12 pre‐miRNAs in viral latency and the development of KSHV‐related malignancies By producing BAC16 miR‐K3 mutant viruses, we previously demonstrated that deletion of miR‐K3 from the KSHV genome attenuated KSHV‐induced cell migration and invasion, and also disrupted KSHV latency and impaired angiogenesis .…”
Section: Discussionmentioning
confidence: 72%